Reinterações hospitalares, custos e qualidade de vida após a alta da unidade de terapia intensiva - Candaten, Angela Enderle (2021)
Introduction: After hospital discharge of critical patients, there is a risk of readmissions due to loads of comorbidities and adverse cognitive and functional sequelae. The objective of this study is to analyze the frequency of hospital readmissions, the total cost and the quality of life after discharge from the Intensive Care Unit (ICU) among patients with and without sepsis. Material and Methods: The research is a retrospective cohort study conducted with 242 patients who survived hospitalization in an Adult Intensive Care Unit in southern Brazil. Results: The main results show that 45% of the patients who survived the ICU admission presented with hospital readmission in 1 year after discharge from the ICU and, after admission to the ICU, the surviving patient costs 64.8% more in the readmissions in one year. As for costs, the condition of having or not sepsis is significantly different (p <0.001) only in the first hospitalization. In hospital readmissions, 1 year after discharge from the ICU, there was no significant difference when comparing the cost between patients with and without sepsis. The overall mortality rate of the sample in this study, in 1 year, was 20.2% (n = 49) and there was no significant difference between the mortality of patients with and without sepsis (p = 0.278). Conclusion: This study suggests an opportunity, both clinical and economic, in the quest to reduce the burden of critical illness. A care model that incorporates personalized physical-cognitive-behavioral interventions, risk-based preventive management, management of chronic health conditions and care objectives aligned with the patient's desire can be viable alternatives for the sustainability of the health system.